Artificial light improves escapement of fish from a trawl net. (10th March 2020) - Southworth, Lucy K.; Ratcliffe, Frances C.; Bloor, Isobel S. M.; Emmerson, Jack; Watson, Dan; Beard, David; Kaiser, Michel J.
Abstract: The elimination of unwanted catch in mixed species fisheries is technically challenging given the complexity of fish behaviour within nets. Most approaches to date have employed technologies that modify the nets themselves or use physical sorting grids within the gear. There is currently increasing interest in the use of artificial light to either deter fish from entering the net, or to enhance their escapement from within the net. Here, we evaluated the differences in catch retained in a standard otter trawl, relative to the same gear fitted with a square mesh panel, or a square mesh panel fitted with LEDs. We found that the selectivity of the gear differed depending on water depth. When using a square mesh panel in shallow depths of 29–40 m the unwanted bycatch of whiting and haddock was reduced by 86% and 58% respectively. In deep, darker water (45–95 m), no change in catch was observed in the square-mesh panel treatment, however when LEDs were added to the square-mesh panel, haddock and flatfish catches were reduced by 47% and 25% respectively. These findings demonstrate the potential to improve the performance of bycatch reduction devices through the addition of light devices to enhance selectivity. The results also highlight species-specific and site-specific differences in the performance of bycatch reduction devices, and hence a more adaptive approach to reduce bycatch is probably required to maximize performance.